Exploring factors for sustainable success of festivals: authenticity, customer satisfaction, and customer citizenship behavior - Jeon, Hyeongjin (Kansas State University, 2018)
Festivals draw large numbers of visitors to tourist destinations and provide stakeholders with monetary and non-monetary benefits. Considering festivals’ positive influence on the host destinations and increasing competition, making festivals continuously successful is critical. However, little empirical work has been conducted that helps destination marketers and festival organizers increase festivals’ competitiveness. Thus, the purpose of this dissertation was to assess the nature of festival attendees’ experiences, and the way in which the experiences contribute to developing attendees’ voluntary behaviors that enable festivals to achieve a competitive advantage. Study 1 examined multiple dimensions of constructive authenticity and relationships among constructive authenticity, existential authenticity, and festival satisfaction. The link to the online survey was distributed by a survey research firm (Qualtrics) to potential participants who had attended at least one Renaissance Festival in the U.S. within the past 12 months. A total of 411 usable responses was collected and included in the final data analyses. The results of an exploratory factor analysis identified three underlying dimensions of constructive authenticity: performance, human, and physical environment. The proposed relationships were tested using structural equation modeling. The results indicated that existential authenticity was positively related to the human (β = .47, t = 5.20, p < .001) and physical environment (β = .43, t = 4.88, p < .001) factors but not to the performance factor. Further, existential authenticity was positively associated with festival satisfaction. Study 2 tested relationships among existential authenticity, festival satisfaction, affective commitment, and three dimensions of attendees’ customer citizenship behavior (CCB): helping others, making recommendations, and providing constructive suggestions to organizers. Responses to a self-administered questionnaire distributed by Qualtrics were collected, and 408 usable responses were used to test the research model proposed. The results showed that existential authenticity was positively related to festival satisfaction (β = .83, t = 15.65, p < .001). However, existential authenticity did not influence CCB. Festival satisfaction was not related directly to helping others, but was related positively to making recommendations (β = .36, t = 3.16, p < .01). Contrary to the prediction, festival satisfaction was associated negatively with providing constructive suggestions. Festival satisfaction was also linked positively with affective commitment (β = .66, t = 13.59, p < .001). The results underscored the positive effect of affective commitment on three dimensions of CCB: helping others (β = .67, t = 10.30, p < .001), making recommendations (β = .15, t = 2.39, p < .05), and providing constructive suggestions (β = .63, t = 9.60, p < .001). In addition, the significance of the indirect effects of existential authenticity on making recommendations via festival satisfaction, as well as festival satisfaction on helping others through affective commitment, was confirmed. The findings advance our understanding of perceived authenticity and CCB in the festival context. In addition to its contributions to the literature, destination marketers and festival organizers can benefit from the suggestions for practical applications. The study concludes with a discussion of its limitations and recommendations for future research.
Keywords: Festival; Constructive authenticity; Existential authenticity; Festival satisfaction; Affective commitment; Customer citizenship behavior